PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS KEARIFAN LOKAL MATERI GELOMBANG BUNYI UNTUK SMA KELAS XI - Jufrida Jufrida; Rahma Dani; Fibrika Rahmat Basuki; Suci Suci Rahma Dwi Astuti (Physics Education Departement Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2022)
The purpose of this study was to develop a learning device based on local wisdom of sound wave material for SMA class XI. This study uses a 4D development model (Define, Design, Develop, Disseminate). The learning tools that have been developed are validated by material experts, media experts, and teachers to determine their feasibility. The research instrument used is a validation sheet. Data were analyzed descriptively. The result of the development of this research is a learning device based on local wisdom of sound wave material for SMA class XI. The feasibility level of the product developed got 94% results in the very good category for material experts, 97% in the very good category for media experts, and 94% in the very good category for teachers. Based on the results of this study, it can be concluded that the product of learning devices based on local wisdom of sound wave material for SMA class XI is feasible to use.